Influence of artistic gymnastics on iron nutritional status and exercise-induced hemolysis in female athletes - Mattos Sureira, T.; Silverio Amancio, O.; Aparecida Pellegrini Braga, J. (International Journal of Sport Nutrition and Exercise Metabolism, 2012)
This study evaluates the relationship between body iron losses and gains in artistic gymnastics female athletes. It shows that despite the low iron intake and exercise-induced hemolysis, iron deficiency or iron-deficiency anemia does not occur, but partial changes in the hematological profile do. The hypothesis that gymnasts` nutritional behavior contributes to anemia, which may be aggravated by exercise-induced hemolysis, led to this cross-sectional study, conducted with 43 female artistic gymnasts 6-16 yr old. The control group was formed by 40 nontraining girls, paired by age. Hemogram, serum iron, ferritin, soluble transferrin receptor, haptoglobin, total and fractional bilirubin, Type I urine, and parasitologic and occult fecal blood tests were evaluated. The athletes presented mean hematimetric and serum iron values (p = .020) higher than those of the control group. The bilirubin result discarded any hemolytic alteration in both groups. The haptoglobin results were lower in the athlete group (p = .002), confirming the incidence of exercise-induced hemolysis. Both groups presented low iron intake. The results suggest that artistic gymnastics practice leads to exerciseinduced hemolysis and partially changes the hematological profile, although not causing iron deficiency or iron-deficiency anemia, even in the presence of low iron intake.